Evaluation of selected metal elements in commercial drinking water and tap water in Peninsular Malaysia - Hock-Eng Khoo,; Azrina Azlan,; Mohd Aizat Idris,; Amin Ismail,; Muhammad Rizal Razman, (Penerbit UKM, 2011)
The present study was carried out to determine the concentrations of selected metal elements (lead, copper, manganese,zinc and iron) in 51 samples of commercial drinking water and tap water available in Malaysia. The results indicated that low metal elements were found in the studied water samples. Lead, manganese, zinc and iron were not detected in some of the studied samples, except copper. The concentrations of the metal elements in the studied samples were well below the maximum permitted concentrations as recommended. Therefore these drinking water are safe for consumption and do not pose adverse effect to the health of consumers due to metal toxicity.